2005
DOI: 10.1677/joe.1.05883
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic hormones a.k.a. hypothalamic releasing factors

Abstract: Originally searched for and eventually isolated as factors of hypothalamic origin controlling anterior pituitary secretions, these hypophysiotropic peptides are now a chapter of physiology and medical endocrinology of their own. Defying the concept of 'neuropeptides' they and their receptors are now known to be ubiquitous and to have subtle as well as profound effects on a large number of functions of both soma and psyche. This review will be composed of brief essays on current knowledge of each of the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(45 citation statements)
references
References 112 publications
(105 reference statements)
0
41
0
3
Order By: Relevance
“…It has since been found to also be produced by the endocrine pancreas and the gastrointestinal tract [58]. The presence of somatostatin receptors on the surface of most NETs makes targeting these receptors a natural therapeutic approach.…”
Section: Somatostatin Analoguesmentioning
confidence: 99%
“…It has since been found to also be produced by the endocrine pancreas and the gastrointestinal tract [58]. The presence of somatostatin receptors on the surface of most NETs makes targeting these receptors a natural therapeutic approach.…”
Section: Somatostatin Analoguesmentioning
confidence: 99%
“…In recent years, somatostatin (SS) and dopamine (DA) receptors have been highlighted as two critical regulators involved in the negative control of hormonal secretion in a wide group of neuroendocrine tumors (NET), including pituitary adenomas (Ben-Jonathan & Hnasko 2001, Guillemin 2005, Ferone et al 2009). Moreover, SS, DA, and their receptors represent two major systems that share a number of structural and functional characteristics (Rocheville et al 2000a, Baragli et al 2007, Srirajaskanthan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence available at that time indicated that stimulation of the central nervous system, but not direct stimulation of the pars distalis or neural lobe, caused the release of adenohypophysial hormones. During the 1950s and 1960s, trophic substances were extracted from the brain of different species (Guillemin, 2005). These releasing factors obtained from the median eminence affected secretions of the pars distalis.…”
Section: Introductionmentioning
confidence: 99%